Behavioral effects of congenital ventromedial prefrontal cortex malformation - Boes Aaron D; Grafft Amanda; Joshi Charuta; Chuang Nathaniel A; Nopoulos Peg; Anderson Steven W (BMC Neurology, 2011)
Abstract Background A detailed behavioral profile associated with focal congenital malformation of the ventromedial prefrontal cortex (vmPFC) has not been reported previously. Here we describe a 14 year-old boy, B.W., with neurological and psychiatric sequelae stemming from focal cortical malformation of the left vmPFC. Case Presentation B.W.'s behavior has been characterized through extensive review Patience of clinical and personal records along with behavioral and neuropsychological testing. A central feature of the behavioral profile is severe antisocial behavior. He is aggressive, manipulative, and callous; features consistent with psychopathy. Other problems include: egocentricity, impulsivity, hyperactivity, lack of empathy, lack of respect for authority, impaired moral judgment, an inability to plan ahead, and poor frustration tolerance. Conclusions The vmPFC has a profound contribution to the development of human prosocial behavior. B.W. demonstrates how a congenital lesion to this cortical region severely disrupts this process.